To determine which equation, when multiplied by 4, would make sense for Kelia's second step, we need to examine each equation:
-
4 + 6x = 1
- If we multiply both sides by 4:
\(4(4 + 6x) = 4(1)\)
- This results in: \(16 + 24x = 4\)
- If we multiply both sides by 4:
\(4(4 + 6x) = 4(1)\)
-
6 + x/4 = 1
- If we multiply both sides by 4:
\(4(6 + x/4) = 4(1)\)
- This results in: \(24 + x = 4\)
- If we multiply both sides by 4:
\(4(6 + x/4) = 4(1)\)
-
4 + x/6 = 1
- If we multiply both sides by 4:
\(4(4 + x/6) = 4(1)\)
- This results in: \(16 + \frac{4x}{6} = 4\)
- Which simplifies to \(16 + \frac{2x}{3} = 4\) (but that does not lead to a clean multiplication scenario for x).
- If we multiply both sides by 4:
\(4(4 + x/6) = 4(1)\)
-
6 + 4x = 1
- If we multiply both sides by 4:
\(4(6 + 4x) = 4(1)\)
- This results in: \(24 + 16x = 4\)
- If we multiply both sides by 4:
\(4(6 + 4x) = 4(1)\)
Since we see that in the second equation, 6 + x/4 = 1, multiplying it by 4 directly influences the term with x, providing a straightforward step to isolate or further manipulate x.
Thus, the equation Kelia is solving is: 6 + x/4 = 1.